Counselees' Perspectives of Genomic Counseling Following Online Receipt of Multiple Actionable Complex Disease and Pharmacogenomic Results: a Qualitative Research Study. Issue 4 (5th December 2016) - Sweet, Kevin; Hovick, Shelly; Sturm, Amy C.; Schmidlen, Tara; Gordon, Erynn; Bernhardt, Barbara; Wawak, Lisa; Wernke, Karen; McElroy, Joseph; Scheinfeldt, Laura; Toland, Amanda E.; Roberts, J. S.; et al.
Abstract: Genomic applications raise multiple challenges including the optimization of genomic counseling (GC) services as part of the results delivery process. More information on patients' motivations, preferences, and informational needs are essential to guide the development of new, more efficient practice delivery models that capitalize on the existing strengths of a limited genetic counseling workforce. Semi‐structured telephone interviews were conducted with a subset of counselees from the Coriell Personalized Medicine Collaborative following online receipt of multiple personalized genomic test reports. Participants previously had either in‐person GC (chronic disease cohort, n = 20; mean age 60 years) or telephone GC (community cohort, n = 31; mean age 46.8 years). Transcripts were analyzed using a Grounded Theory framework. Major themes that emerged from the interviews include 1) primary reasons for seeking GC were to clarify results, put results into perspective relative to other health‐related concerns, and to receive personalized recommendations; 2) there is need for a more participant driven approach in terms of mode of GC communication (in‐person, phone, video), and refining the counseling agenda pre‐session; and 3) there was strong interest in the option of follow up GC. By clarifying counselees' expectations, views and desired outcomes, we have uncovered a need for a more participant‐driven GC model when potentially actionable genomic results are received online.